2011
DOI: 10.4236/ijg.2011.24041
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Estimation of Coastal Changes Along Selected Locations of Karnataka, India: A GIS and Remote Sensing Approach

Abstract: Qualitative and quantitative studies on changes of coastal geomorphology and shoreline of Karnataka, India have been carried out using toposheets of Survey of India and satellite imageries (IRS-P6 and IRS-1D). Changes during 30 years period are studied at each station. Significant morphological changes in landforms like spit, channel Island, coastal plain, tidal flat, lateritic plain, alluvial plain and sand bar within and adjcent to estuarine river mouths of Kali, Sharavathi, Kollur-Chakkara - Haladi and Udya… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 5 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…Soil erosion is one of the important land degradation problems in agricultural land and consider as critical environmental hazard in modern time, worldwide (Lu et al, 2003;Kim et al, 2005). It is one of the most serious problems as it removes plant essential nutrients from the top soil and increases natural level of sedimentation in rivers and reservoirs which in turn reduce their storage capacity and water availability to plants (Devatha et al, 2015).The coastal systems have different kind of ecological problems due to various anthropogenic and natural interventions and regular prone to different kinds of erosion, sedimentation, floods and cyclones (Vinayaraj et al, 2011;Monalisha and Panda, 2018). Coastal ecosystems provide livelihood to around 60% of world's population.…”
Section: Introductionmentioning
confidence: 99%
“…Soil erosion is one of the important land degradation problems in agricultural land and consider as critical environmental hazard in modern time, worldwide (Lu et al, 2003;Kim et al, 2005). It is one of the most serious problems as it removes plant essential nutrients from the top soil and increases natural level of sedimentation in rivers and reservoirs which in turn reduce their storage capacity and water availability to plants (Devatha et al, 2015).The coastal systems have different kind of ecological problems due to various anthropogenic and natural interventions and regular prone to different kinds of erosion, sedimentation, floods and cyclones (Vinayaraj et al, 2011;Monalisha and Panda, 2018). Coastal ecosystems provide livelihood to around 60% of world's population.…”
Section: Introductionmentioning
confidence: 99%
“…The abrasion condition in this regency is also exacerbated by the development of shrimp ponds that affect the vulnerability of the land around the coast. Coastal areas that experience abrasion for an extended period will cause disruption of local sediment dynamics [5] caused by nature and humans [6]. Abrasion, a global problem [7,8] is caused by high-intensity waves and currents [9].…”
Section: Introductionmentioning
confidence: 99%
“…Figure5 The shoreline of Central Bengkulu changes as one progresses along the coast. Gedang Lake is in Zone I. Sungai Suci and Wahana Surya coastlines are in Zone II.…”
mentioning
confidence: 99%
“…Satellite Remote Sensing, with its unique capability of providing repetitive, dynamic and global coverage at high temporal and spatial resolution, is very useful for the analysis of changes taking place in the coastal areas [5]. The major advantage of GIS is that it allows identifying the spatial relationships between features and temporal changes within an area over time [6]. Experience has shown that many earth surface features of interest can be identified, mapped and studied on the basis of their spectral characteristics, although some features of interest may not be spectrally separable.…”
Section: Introductionmentioning
confidence: 99%